Al-Umuru Bimaqasidiha: Bagaimana Implementasinya dalam Muamalah? - Khusnul Fikriyah (Nomicpedia: Journal of Economics and Business Innovation, 2021)
Fiqh rules are part of the way of implementing the law. With this understanding of the principles of fiqh the application of fiqh in a different scope, at a certain time and at different locations for various problems, cultural cultures, and different conditions. With the principles of fiqh, humans will be more moderate in responding to the problems that continue to arise and develop in society. In this article, the author will discuss Al-Umuru Bimaqasidiha. This rule discusses the position of intention which is very important in determining the quality or meaning of one's actions. The method used is library research, with a qualitative descriptive approach.